Cranioplasty: The autograft option - Viterbo, Fausto [UNESP]; Palhares Neto, Aristides Augusto [UNESP]; Modenese, E. [UNESP] (My University, 1995)
We present our clinical experience in cranioplasty with autograft as follows: conchal cartilage for losses up to 2 cm2, outer table grafts for defects up to 100 cm2, and, for larger defects still, split rib grafts, which may be combined with outer table grafts. We conclude that autograft is superior to alloplastic material in cranioplasty.
Keywords: Autograft; Cranioplasty; Outer table parietal grafts; adult; aged; allograft; autograft; cartilage graft; clinical article; cranioplasty; female; human; male; priority journal; rib graft; school child; skull injury; bone transplantation; cartilage; child; comparative study; craniotomy; methodology; middle aged; plastic surgery; skull; transplantation; Adult; Aged; Bone Transplantation; Cartilage; Child; Craniotomy; Female; Humans; Male; Middle Aged; Parietal Bone; Skull; Surgery, Plastic